Cutting carbon footprints of vegetable production with integrated soil - crop system management: A case study of greenhouse pepper production. (1st May 2020) - Wang, Xiaozhong; Liu, Bin; Wu, Gang; Sun, Yixiang; Guo, Xisheng; Jin, Guoqing; Jin, Zhenghui; Zou, Chunqin; Chadwick, Dave; Chen, Xinping
Abstract: In China there is an urgent need to improve the sustainability of vegetable production by increasing yields and reducing the environmental losses. However, whilst various single nutrient management measures have proved successful at reducing environmental losses, they have not simultaneously increased yield. Here, we report on a three-year field experiment that used an integrated soil - crop system management (ISSM) approach, to improve crop (pepper) yield and to cut carbon (C) and nitrogen (N) footprints of greenhouse vegetable production in the Yangtze River Basin, China. Treatments included farmers' practice (FP) for nutrient inputs, soil and crop management; soil remediation (SR), as a single factor approach to optimize soil management, including control of soil borne pathogens and reduced nutrient input by organic resources; and ISSM, as a systematic integrated approach, which includes the combined optimization of factors, including soil remediation, reduced planting density, and improved timing of inorganic fertilizer applications (rate and form). Measurements of pepper yield and N concentrations were used to calculate N offtake, and the C and N footprints were then calculated using life cycle assessment. The three-year continuous field experiment indicated that the mean pepper yield (fresh weight) from the ISSM treatments were 48 t ha −1, 17% and 10% greater than that of the FP and SR treatments (p < 0.05), respectively. The reactive nitrogen (Nr) losses from the FP, SR, and ISSM treatments were 82, 52 and 59 kg N ha −1, respectively. The greenhouse gas emissions of FP, SR, and ISSM treatments were 7061, 5279 and 5728 kg CO2 -eq ha −1, respectively. The N and C footprints of the ISSM treatment were significantly lower than the FP treatment by 39% and 30%, respectively, as a result of both a 46% reduction in N inputs (especially an 80% reduction in organic N inputs) and a greater yield. The yield increase contributed to 26% and 37% the reduction of N and C footprints in ISSM treatment, respectively. Meanwhile, there were no significant difference in the N and C footprints between SR and ISSM. This study highlights that the ISSM strategy can produce greater pepper yields with lower environmental costs, and can contribute to sustainable greenhouse vegetable production, and that SR, whilst being a single factor strategy, is a useful first step towards ISSM. Graphical abstract: Image 1 Highlights: Integrated soil-crop system management (ISSM) increased fruit yield by 17% compared to farmers' practice (FP). ISSM reduced the nitrogen (N) inputs by 46%, compared to FP. ISSM reduced greenhouse gas emission by 19% and the carbon (C) footprint by 30%, compared to FP. ISSM increased the fruit yield by 10% with a similar C footprint, compared to soil remediation alone. Reducing excessive N inputs and improving yields were critical measures to reduce the C footprint.